Reflections on Being a Learner: The Value of Relationship-based Community Evaluations in Indigenous Communities - McKinley, Gerald (Canadian Journal of Program Evaluation, 2020)
Drawing on Donna M. Mertens and Amy T. Willson’s work on transformative paradigms in program evaluations together with the authors experience working in partnership with First Nations communities in Ontario, Canada this paper explores the lessons learned from the process of moving between assumptions and application using the transformative paradigm in First Nations evaluations; explores the relationships between power, discourse and paradigms in the relationship between Western and Indigenous ways of knowing and Being; and, asks what steps can an evaluator take to ensure that local epistemological and ontological perspectives are respected and captured. S'appuyant sur les travaux de Donna M. Mertens et Amy T. Willson sur les paradigmes de transformation dans les évaluations de programmes, ainsi que sur l'expérience des auteurs de travailler en partenariat avec les communautés des Premières nations de l'Ontario, au Canada, cet article explore les leçons tirées du processus de transition entre hypothèses et applications en utilisant le paradigme de transformation dans les évaluations des Premières nations; explore les relations entre le pouvoir, le discours et les paradigmes dans la relation entre les modes de connaissance et d'être occidentaux et autochtones; et, demande quelles mesures un évaluateur peut-il prendre pour s'assurer que les perspectives épistémologiques et ontologiques locales sont respectées et prises en compte.